Homoeopathic Management in a Case of Infertility with PCOS - Rath, Padmalaya; Gautam, Shweta (Homœopathic Links, 2021)
Infertility is the inability of a sexually active couple, not using any birth control, to get pregnant after 1 year of trying. About one-quarter of female infertility is caused by a problem with ovulation. Polycystic ovary syndrome (PCOS) accounts for more than 75% of cases of anovulatory infertility. PCOS is a disorder of chronically abnormal ovarian function and hyperandrogenism (abnormally elevated androgen levels) manifested by irregular menstrual cycles, polycystic ovaries, excess unwanted hair, obesity etc. A case of a female aged 21 years with irregular menses for the past 2 years diagnosed with PCOS and inability to conceive has been reported here. The case was worked out as per homoeopathic principles and individualised homoeopathic medicine, Pulsatilla nigricans (Puls. nig.) was prescribed and the patient responded positively and conceived
Keywords: anovulatory infertility; infertility; individualised homoeopathic medicine; polycystic ovary syndrome; Pulsatilla nigricans